2005
DOI: 10.1097/01.aog.0000148264.20909.bb
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hemodynamics After Oxytocin Bolus Compared With Infusion in the Third Stage of Labor: A Randomized Controlled Trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 8 publications
2
38
0
1
Order By: Relevance
“…Particularly when given as a bolus, oxytocin can cause a precipitous drop in blood pressure, even leading to cardiac arrest. [1][2][3][4][5] An arterial line allows continuous real-time display of arterial pressure and convincing reports of the profound effects of bolus oxytocin on arterial blood pressure and pulse rate have been published. 1,2 Table 1 shows that hemodynamic changes following delivery were all in the same directions as those following oxytocin, though the oxytocin-induced changes were greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly when given as a bolus, oxytocin can cause a precipitous drop in blood pressure, even leading to cardiac arrest. [1][2][3][4][5] An arterial line allows continuous real-time display of arterial pressure and convincing reports of the profound effects of bolus oxytocin on arterial blood pressure and pulse rate have been published. 1,2 Table 1 shows that hemodynamic changes following delivery were all in the same directions as those following oxytocin, though the oxytocin-induced changes were greater.…”
Section: Discussionmentioning
confidence: 99%
“…Because SVR is not directly monitored, clinicians usually observe a decrease in mean arterial pressure (MAP); when given as a bolus, oxytocin can cause significant reductions in MAP. [1][2][3][4][5] Mean arterial pressure (MAP) is (approximately) the product of CO and SVR. Oxytocin decreases maternal blood pressure most commonly through a reduction in SVR; but, a reduction in venous return through the dilatation of capacitance vessels can also occur.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Table 2, but when we gave oxytocin to this patient we saw that a 9% decrease in mean arterial pressure (MAP) was accompanied by a 40% decrease in SVR and a 48% increase in CO. Since oxytocin administration has been associated with severe hypotension and even death in hypovolemic patients [8,9,[16][17][18][19], we were reassured as to the patient's volume status by the fact that the CO was able to increase appropriately in the face of a decrease in SVR caused by oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…A few minutes later, after vigorous administration of phenylephrine and intravascular fluid, a fall in SVR was accompanied by a rise in CO. Oxytocin is known to cause both arteriolar and venous dilation. 8,9 PulseCO readings suggested that it did both.…”
Section: Discussionmentioning
confidence: 99%